2011
DOI: 10.1007/s10585-011-9414-8
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CD44 by siRNA suppressed invasion, migration and adhesion to matrix, but not secretion of MMPs, of cholangiocarcinoma cells

Abstract: We studied the expression pattern and the role of CD44 in regulating the malignant behavior of two cholangiocarcinoma (CCA) cell lines which expressed different levels of CD44 using the siRNA technique. KKU-100, the high CD44 expresser, exhibited a high degree of in vitro invasiveness, migration and adhesion to Matrigel compared to HuCCA-1. Silencing of CD44 by siRNA did not have a significant effect on cell proliferation. However, in vitro invasiveness, directional migration (chemotaxis) and adhesion to Matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Gelatinase activity of MMP-2 was assessed using gelatin zymography as previously described [26]. C33A stably expressing different oncoproteins were incubated in serum-free medium for 48 h before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Gelatinase activity of MMP-2 was assessed using gelatin zymography as previously described [26]. C33A stably expressing different oncoproteins were incubated in serum-free medium for 48 h before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the RNA interference-based blockage of EpCAM in hepatic stem/progenitor cells induced a decrease in tumorigenicity and invasiveness [34,61]. Recent studies also revealed that CD44 silencing by siRNA has a significant effect on invasiveness, migration, and adhesion in cholangiocarcinoma cell lines [62]. Moreover, CD24 inhibition using siRNA significantly decreased the invasive capacity of cholangiocarcinoma cells [28].…”
Section: A Possible Targeted Therapy For Cholangiocarcinoma Stem Cellsmentioning
confidence: 99%
“…Cancer stem cells, which possess stem cell‐like characteristics, including multilineage and self‐renewal potentials, have been identified in cancer tissues . Previous studies reported that tumor progression, metastasis, and resistance to anticancer therapy were driven by CSCs, which were identified by cell surface markers such as CD44 . CD44 exists in numerous variant isoforms generated through the alternative mRNA splicing of different combinations of 10 exons (v1‐10), and the variant isoforms of CD44 containing v8‐v10 (CD44v9) have been identified as new cell surface markers of CSCs .…”
Section: Introductionmentioning
confidence: 99%